2011
DOI: 10.1097/wnr.0b013e32834cd76a
|View full text |Cite
|
Sign up to set email alerts
|

Site-specific subtypes of macrophages recruited after peripheral nerve injury

Abstract: After partial ligation of mouse sciatic nerve, the subtypes of macrophages were examined in the injured nerve and dorsal root ganglia (DRGs). Many M1 macrophages, which were inducible nitric oxide synthase (iNOS)-positive and arginase-1 (Arg-1)-negative, and neutrophils infiltrated the injured nerve. In contrast, almost all macrophages infiltrating the ipsilateral side of DRGs after the nerve injury were iNOS⁻/Arg-1⁺, M2 type. The infiltration of M1 and M2 macrophages was first observed in the injured nerve an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
53
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(61 citation statements)
references
References 24 publications
6
53
0
2
Order By: Relevance
“…It has been shown previously that there is an increase in the number of macrophages in the ganglia after nerve injury (Lu and Richardson, 1993), and that a portion of these are infiltrating circulating macrophages (Scholz and Woolf, 2007). The number of macrophages in the ganglia starts to increase 3 days post-nerve injury (Komori et al, 2011) and peaks at 8 days (Lu and Richardson, 1993). We did not find circulating macrophages with BrdU labeled nuclei in the ganglia indicating that this population of macrophages is terminally differentiated.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown previously that there is an increase in the number of macrophages in the ganglia after nerve injury (Lu and Richardson, 1993), and that a portion of these are infiltrating circulating macrophages (Scholz and Woolf, 2007). The number of macrophages in the ganglia starts to increase 3 days post-nerve injury (Komori et al, 2011) and peaks at 8 days (Lu and Richardson, 1993). We did not find circulating macrophages with BrdU labeled nuclei in the ganglia indicating that this population of macrophages is terminally differentiated.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Nadeau et al (2011) found monocyte derived M1 macrophages present early after nerve injury but they were gone by 3-4 d, the same time point at which macrophages at the injury site begin to express anti-inflammatory, M2 associated markers such as arginase 1 and CD206. In addition, Komori et al (2011) found that at 1 and 3 d after partial nerve ligation, the immune response was characterized byM1 macrophages in the nerve (i.e. iNOS positive and arginase 1 negative), whereas the DRG contained M2 macrophages.…”
Section: The Biology Of Wallerian Degenerationmentioning
confidence: 98%
“…These cells also have high phagocytic activities. [38][39][40][41][42][43][44] The differentiation of M2 macrophages is promoted by different molecules such as IL-4, IL-6, IL-10, IL-13, vascular endothelial growth factor, and prostaglandin E2 (PGE2). M2 macrophages play a major role in resolving inflammation, degrading scar, and remodeling tissue by secreting trophic factors and releasing IL-10.…”
mentioning
confidence: 99%